1974
DOI: 10.1073/pnas.71.6.2342
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of the Major Viral Glycoprotein and a Putative Precursor from Cells Transformed by Avian Sarcoma Viruses

Abstract: Immune precipitation with a monospecific antiserum was employed to study the synthesis of the major viral glycoprotein gp85. Labeled gp85 was detectable by polyacrylamide gel electrophoresis of immune precipitates prepared from lysates of transformed cells which had been labeled for long term with radioactive amino acid or fucose. When immune precipitates were prepared from lysates of cells pulse-labeled with radioactive amino acid, the bulk of the precipitated counts did not appear in gp85 but in a heterogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

1976
1976
1982
1982

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 14 publications
1
28
0
Order By: Relevance
“…Halpern et al (10) have provided some evidence that the precursor to avian sarcoma virus gp85 is a 70,000 dalton subglycosylated species lacking fucose. In addition, under conditions which limit glycosylation of glycoproteins, anti-gp85 recognized a second carbohydrate deficient form of gp85 (11) which has different properties than the above 70,000 dalton precursor in that it contains fucose.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Halpern et al (10) have provided some evidence that the precursor to avian sarcoma virus gp85 is a 70,000 dalton subglycosylated species lacking fucose. In addition, under conditions which limit glycosylation of glycoproteins, anti-gp85 recognized a second carbohydrate deficient form of gp85 (11) which has different properties than the above 70,000 dalton precursor in that it contains fucose.…”
Section: Discussionmentioning
confidence: 99%
“…* anti-gp69/71 serum was used, 5-10 Al of antiserum were added to the extract followed by a 30 min incubation at 37°. After a subsequent incubation at 40 for [4][5][6][7][8][9][10][11][12] hr, 0.1-0.2 ml of goat anti-rabbit globulin or rabbit anti-goat globulin were added, respectively, and the incubation continued at 40 for [4][5][6][7][8][9][10][11][12] hr. The precipitates were collected by centrifugation, washed several times by resuspension and centrifugation, and analyzed by sodium dodecyl sulfate/polyacrylamide gel electrophoresis (NaDodSO4/electrophoresis) (3).…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported by several laboratories that the primary translational product of the e m gene of mammalian type-C viruses is a glycosylated protein of approximately 82,000-85,000 daltons, which is the precursor for the major viral glycoprotein, gp70 (17,20,44), and probably contains a smaller molecular weight nonglycosylated surface protein, p l 5 ( E ) (17, For avian viruses, a glycoprotein designated Pr90 was identified by immune precipitation with antiserum to gp85 (16), which is subsequently cleaved to yield the major, fully glycosylated envelope glycoprotein, gp85. Previous studies of the same group showed the presence of a 70,000-dalton nonglycosylated or weakly glycosylated protein by pulse-chase experiments (27). It is now believed that Pr70 is an incompletely formed molecular species of Pr90 (16).…”
Section: Products Of the Enu Genementioning
confidence: 94%
“…Wild-type virus exhibited the normal glycoprotein profile (lane G), but mutant virus (lane H) lacked detectable gp85 and gp37. A glycosylated protein related to gp85 of 70,000 daltons, identified as an incompletely glycosylated envelope precursor, has been found in RSV-infected chicken (11,23) and quail (23) cells. In our gel system this precursor migrates as a band of 60,000 to 65,000 daltons.…”
mentioning
confidence: 99%